CONSTRUCTION GUARANTEES: FINALLY CLOSING THE DOOR ON EXTRANEOUS DEFENCES Coface South Africa Insurance Co Ltd v East London Own Haven t/a Own Haven Housing Association 2014 (2) SA 382 (SCA) - Christiaan Swart (Obiter, 2014)
The issuing of performance bonds or construction guarantees in terms of a building contract may hold important consequences for the parties to a construction guarantee. Recently construction guarantees have received much attention from our courts and some of these cases even proceeding to the Supreme Court of Appeal. There may be various reasons for this sudden escalation in litigation with construction guarantees as the subject matter. One of the reasons may be due to numerous major construction projects that have been undertaken in the last few years in South Africa. Notable examples of these major construction projects include the building of stadia for the 2010 FIFA Soccer World Cup, the Gautrian Project, and the Gauteng Freeway Improvement Project. One of the aspects of construction guarantees that our courts has had to deal with was the nature of construction guarantees. The nature of construction guarantees is not only of academic interest but also has very important practical implications. Building, engineering and construction contracts such as the family of New Engineering Contracts and The Joint Building Contracts Committee agreements make provision for the employer or the party commissioning the construction works (“the works”’) to place a contractual obligation on the contractor to furnish a construction guarantee. Shortly after the award of the construction contract (“the underlying contract”), the contractor will instruct its insurer or banker to issue such a construction guarantee to the benefit of the employer. From the employer’s perspective, the construction guarantee serves a dual purpose: firstly, the willingness of a financial institution or insurer to issue such a construction guarantee is, to a degree, an indication of the contractor’s financial welfare. Secondly, in the event of the contractor’s default, the construction guarantee enables the employer to gain immediate access to funds to properly complete the works in terms of the underlying contract. A contractual relationship is created by the construction guarantee between the employer and the issuer thereof. When properly drafted, a construction guarantee entitles an employer to demand payment from the issuer unconditionally upon the occurrence of a specific event. The liability of the issuer of the construction guarantee is subject only to the employer complying with the terms and conditions contained in the construction guarantee. Normally, the employer is required to issue a certificate in terms of which it is confirmed that the contractor is in default of the building contract or underlying contract and therefore the employer demands payment in terms of the construction guarantee. The main advantage that a construction guarantee offers to an employer is when enforcing the construction guarantee, the issuer thereof may not raise defences of an extraneous nature. This prevents protracted litigation over complex factual disputes. Fraud in such circumstances that makes it obvious is the only defence the issuer of a construction guarantee may raise to avoid liability under the construction guarantee. However, the Supreme Court of Appeal in Dormell Properties 282 CC v Renasa Insurance Co Ltd reopened again the possibility of raising extraneous defences. The Dormell judgment caused much uncertainty on whether extraneous defences may be raised to avoid liability in terms of a construction guarantee. The confusion regarding the true legal position was further exacerbated by the fact that in subsequent cases involving construction guarantees, the Supreme Court of Appeal chose not to overturn the Dormell case but rather to distinguish the facts of subsequent cases from Dormell. This case note therefore deals with the latest reported judgment on construction guarantees delivered by the Supreme Court of Appeal in Coface South Africa insurance Co Ltd v East London Own Haven t/a Own Haven Housing Association (2014 (2) SA 382 (SCA)). This case is of particular interest because the Supreme Court of Appeal unequivocally held that its judgment in Dormell was clearly wrong. This judgment has now once and for all put the question of whether or not extraneous defences may be raised in order to avoid liability under a construction guarantee to bed. The court also once again confirmed that the English doctrine of consideration does not form part of the South African law of contract.